Student's Attitudes on the Performance and Behavior of Administrative Officers at Universitas Negeri Makassar - Febrilia Ade Putri; Rifdan Rifdan; Lukman Lukman; Zainatun Zainatun (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Universities in Indonesia are taking part in the transformation process and using an entrepreneurial approach to serve students in the new competitive environment better. This article seeks to determine student attitudes toward developing the university. It makes an effort to offer universities some suggestions to improve their performance. A random sample of employees at Makassar State University was interviewed to see their views on the services offered and the perceived quality. To meet deadlines and build deeper with local economic and productive systems, Makassar State University administration should focus on improving the quality of instructional services and non-teaching employees. Makassar State University administrative staff needs to have a student-focused mindset. To assess attitudes towards recent changes at Makassar State University.